ETIKA DALAM PENELTIAN ILMIAH - Yumesri Yumesri; Risnita; Sudur; Asrulla (LPPM Universitas Cipta Mandiri, 2024)
This study aims to describe the basic principles of ethics in a scientific study. The method used in conducting this research is the Library Research method or literature research by collecting various kinds of data and literacy needed for this research. The results of this study are: 1) The basic principles of ethics in scientific research, namely, respect & respect the dignity of human beings as research subjects, Respect the privacy and confidentiality of research subjects, uphold the principles of fairness & equality, take into account the positive and negative impacts of research. 2) Ethics of researchers in scientific research, namely: honesty, objectivity, integrity, accuracy, social responsibility, competence and legality. 3) Ethics of researchers to respondents, assistants and clients. 4) Ethical violations in scientific research, including: fabrication, falsification, plagiarism and conflict of interest. A researcher should apply basic ethical principles in scientific research in order to produce good research worthy of publication.